IL‐33‐expanded human Vγ9Vδ2 T cells have anti‐lymphoma effect in a mouse tumor model. Issue 12 (29th September 2017) - Duault, Caroline; Betous, Delphine; Bezombes, Christine; Roga, Stéphane; Cayrol, Corinne; Girard, Jean‐Philippe; Fournié, Jean‐Jacques; Poupot, Mary
Abstract: From several years, the anticancer effects of Vγ9 T lymphocytes make these cells good candidates for cancer immunotherapies. However, the proved efficacy of γδ Τ cell‐based cancer immunotherapies in some clinical trials was minimized due to the inherent toxicity of IL‐2, which is essential for the combination therapy with Phosphoantigen (PAg). Recently, we showed that IL‐33, a γ chain receptor‐independent cytokine, was able to induce the in vitro proliferation of PAg‐activated Vγ9 T cells, which were fully functional expressing IFN‐γ and TNF‐α and showing in vitro anti‐tumor cytotoxicity. We proposed IL‐33 as an alternative to IL‐2 for Vγ9 T cell‐based cancer immunotherapies, and have therefore evaluated the efficacy of this cytokine in preclinical investigations. This study shows that human Vγ9 T cells are able to proliferate in a mouse model with the combination of PAg and rhIL‐33, and that IL‐33‐expanded Vγ9 T cells can prevent tumor growth in a mouse lymphoma model. Abstract : IL‐33 is able to induce proliferation of phosphoantigen‐activated Vγ9Vδ2 T lymphocytes from human peripheral blood mononuclear cell. These amplified lymphocytes injected to mice with tumor cells avoid tumor development compared to xenograft without IL‐33 amplified Vγ9Vδ2 T lymphocytes. IL‐33 combined to phosphoantigen is thus a good candidate for anticancer Vγ9Vδ2 T cell‐based immunotherapy.